DERBEND-NAMEH (translated by Aliyara b. Kazim from Turkish to Persian) - Alibekova, P M (History, Archeology and Ethnography of the Caucasus, 2015)
The article introduces into scientific use the text of Aliyar b. Kazim’s historical work “Derbend-nameh” in the Persian language that was not translated into Russian before. Aliyar b. Kazim’s writing “Darband-name” is of scientific interest as it provides information that supplements and specifies the material contained in the famous lists of this work.